Recombinant expression and characterisation of the oxygen-sensitive 2-enoate reductase from Clostridium sporogenes - Mordaka, Pawel M.; Hall, Stephen J.; Minton, Nigel P.; Stephens, Gill (Microbiology Society, 2017)
‘Ene’-reductases have attracted significant attention for the preparation of chemical intermediates and biologically active products. To date, research has been focussed primarily on Old Yellow Enzyme-like proteins, due to their ease of handling, whereas 2-enoate reductases from clostridia have received much less attention, because of their oxygen sensitivity and a lack of suitable expression systems. A hypothetical 2-enoate reductase gene, fldZ, was identified in Clostridium sporogenes DSM 795. The encoded protein shares a high degree of homology to clostridial FMN- and FAD-dependent 2-enoate reductases, including the cinnamic acid reductase proposed to be involved in amino acid metabolism in proteolytic clostridia. The gene was cloned and overexpressed in Escherichia coli. Successful expression depended on the use of strictly anaerobic conditions for both growth and enzyme preparation, since FldZ was oxygen-sensitive. The enzyme reduced aromatic enoates, such as cinnamic acid or p-coumaric acid, but not short chain unsaturated aliphatic acids. The b,b-disubstituted nitroalkene, (E)-1-nitro-2-phenylpropene, was reduced to enantiopure (R)-1-nitro-2-phenylpropane with a yield of 90 %. By contrast, the a,b-disubstituted nitroalkene, (E)-2-nitro-1-phenylpropene, was reduced with a moderate yield of 56% and poor enantioselectivity (16% ee for (S)-2-nitro-1-phenylpropane). The availability of an expression system for this recombinant clostridial 2-enoate reductase will facilitate future characterisation of this unusual class of ‘ene’-reductases, and expand the biocatalytic toolbox available for enantioselective hydrogenation of carbon-carbon double bonds.